2015
DOI: 10.1680/geng.14.00004
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the plastic limit of fine soils: an experimental study

Abstract: The Casagrande thread-rolling method for determining the plastic limit of fine-grained soil is heavily dependent on operator judgement and can often give inconsistent or unreliable results. This paper presents an energy-based approach used in the development of an improved testing procedure for the plastic strength limit. A 0·727 kg cone is allowed to fall freely through 200 mm before contacting the surface of the test specimen, with the plastic strength limit determined for a cone penetration depth of 20 mm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 15 publications
0
33
0
1
Order By: Relevance
“…using the 80 g 30°cone in accordance with BSI (1990a)), the plastic strength limit PL 100 (Haigh et al, 2013;Kyambadde and Stone, 2012;Sivakumar et al, 2015) and the undrained shear strength of intact and remoulded clay for different water contents within the plastic range (e.g. using the 80 g 30°(BSI, 1990a), 100 g 30°or 400 g 30°cones (Geonor, 2015)) and to determine sensitivity (i.e.…”
Section: Fall Cone Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…using the 80 g 30°cone in accordance with BSI (1990a)), the plastic strength limit PL 100 (Haigh et al, 2013;Kyambadde and Stone, 2012;Sivakumar et al, 2015) and the undrained shear strength of intact and remoulded clay for different water contents within the plastic range (e.g. using the 80 g 30°(BSI, 1990a), 100 g 30°or 400 g 30°cones (Geonor, 2015)) and to determine sensitivity (i.e.…”
Section: Fall Cone Approachesmentioning
confidence: 99%
“…For typical inorganic soils (m = 0·1, where m is the rate dependence parameter) and cone penetration depths ranging from 5 to 15 mm, the 400 g 60°fall cone provides for strength determinations covering the range of 5-50 kPa (O'Kelly, 2016b). Using the concept presented by Sivakumar et al (2015), O'Kelly (2016b) suggested that a lighter 60°cone which incorporates a falling distance (i.e. before the cone tip contacts the test specimen surface) can be used to achieve the same effect.…”
Section: Fall Cone Approachesmentioning
confidence: 99%
“…Simply based on analysis of historical data, as the ratio of strengths at the PL and LL varies substantially between soils, these strength-based approaches can only coincidentally give correct PL values, actually measuring what might be termed the plastic strength limit (PL 100 ); that is the water content corresponding to s uFC ¼ 100 Â s uFC(LL) . Fall cone Belviso et al, 1985;Wasti, 1987;Harison, 1988;Feng, 2000Feng, , 2001Feng, , 2004Koumoto & Houlsby, 2001;Sharma & Bora, 2003;Lee & Freeman, 2009;Shimobe, 2010;Sivakumar et al, 2015), steady monotonic penetration (Stone & Phan, 1995;Stone & Kyambadde, 2007), fast-static loading (Sivakumar et al, 2009) and extrusion (Timár, 1974;Whyte, 1982;Medhat & Whyte, 1986;Kayabali & Tufenkci, 2010a, 2010bKayabali, 2011aKayabali, , 2011bKayabali, , 2012Kayabali et al, 2016) approaches for PL determination have all been suggested as alternatives to the standard thread-rolling approach. As mechanical tests, these strength-based approaches are seen by some researchers as means of achieving higher degrees of repeatability and reproducibility of results, although, to date, most fall-cone research has been conducted on well-behaved clay-rich soils that lie above the A-line on the standard plasticity chart.…”
Section: Strength-based Approachesmentioning
confidence: 99%
“…Having recognised the important distinction between the true PL and that measured by strength-based tests, the 'PL' determined by the fall-cone approach has been referred to as the 'plastic strength limit' (Haigh et al, 2013) PL 100 (Harison, 1988;Stone & Phan, 1995;Stone & Kyambadde, 2007;Kyambadde & Stone, 2012;Haigh et al, 2013;O'Kelly, 2013;Kyambadde et al, 2014;Sivakumar et al, 2015Sivakumar et al, , 2016, with the subscript 100 indicating that the defined strength is 100 times the strength mobilised for the fall-cone LL (s uFC(LL) ). This assumes that cones having identical apex angle and surface roughness values are used in identifying both LL FC and PL 100 , and, furthermore, that the strain-rate dependency of the soil remains the same (as considered in the next section).…”
Section: Other Factors Influencing Deduced Atterberg Limit Valuesmentioning
confidence: 99%
See 1 more Smart Citation